Responses to Targeted Therapy among Organs Affected by Metastasis in Patients with Renal Cell Carcinoma are Organ-Specific - Jiang, Weixing; Shi, Hongzhe; Zhang, Lianyu; Zhang, Jin; Bi, Xingang; Wang, Dong; Wen, Li; Li, Changling; Ma, Jianhui; Shou, Jianzhong (Urology Journal, 2020)
Purpose: Previous reports showed that targeted therapy efficacy varied due to different metastatic organs in patients with metastatic renal cell carcinoma (mRCC). This study aimed to further evaluate the response and progression-free time (PFT) of individual metastatic organs. Materials and Methods: Data from mRCC patients, who were treated with sunitinib between January 2008 to December 2018, were retrospectively reviewed. Individual metastatic organs were assessed separately by The Response Evaluation Criteria in Solid Tumors criteria. Results: We evaluated response heterogeneity and PFT as characteristics of 281 individual organs affected by mRCC in 213 patients. The objective response rates in these organs were 72.7% in pancreas, 63.7% in spleen, 14.3% in adrenal glands, 13.5% in bone and soft tissue, 11.6% in lymph nodes, 11.6% in lungs, and 9.1% in liver. The median PFT was 15.2 months (95% confidence interval [CI] 2.7–27.7 months) for adrenal glands, 13.2 months (95% CI 3.5–22.9 months) for bone and soft tissue, 9.0 months (95% CI 7.6–10.4 months) for lymph nodes, 8.6 months (95% CI 6.3–10.9 months) for lungs, and 5.2 months (95% CI 2.9–7.5 months) for liver. Median PFT was not reached in pancreas and spleen, but was > 22.8 months and > 20.6 months, respectively. Conclusion: Our results indicated that organs affected by metastasis may have individual responses to sunitinib treatment. The pancreas and spleen may have the best responses, and liver may have the worst response. Further research is needed to verify these findings.